An in-vitro study of temperature rise during rotary ultrasonic bone drilling of human bone. (May 2020) - Singh, Ravinder Pal; Pandey, Pulak Mohan; Mridha, Asit Ranjan
Highlights: Novel operation theatre compatible machine was developed which works on principle of rotary ultrasonic bone drilling (RUBD) process. RUBD produced comparatively lesser temperature rise (from 13.1 °C to 25.8 °C) than CSBD (34 °C to 45 °C) during drilling of hard tibia bones. Design of experiment based response surface methodology was used to plan the set of experiments to study the effect of drilling parameters on temperature rise in RUBD process. Regression equation has been used to develop the statistical model to predict the temperature rise at the bone tool interface, and the drilling parameters (rotational speed, feed rate, drill tool diameter and abrasive size) are determined for minimum temperature rise. Abstract: Temperature rise in surgical bone drilling is an important factor that leads to death of the bone cells, known as Osteonecrosis, and results into poor osteosynthesis i.e. implant failure. The present work aims to study the temperature rise during bone drilling by a recently developed operation theatre (OT) compatible machine. The temperature during the drilling process was recorded from K-type thermocouple devices, which were embedded in the human tibial bone at four different positions (at 0.5 mm, 1.0 mm, 1.5 mm, and 2.0 mm) from the drilling site. Comparative study revealed that rotary ultrasonic bone drilling (RUBD) technique produced lesser temperature (40 – 50%) than conventional drilling on human tibia. Statistical model was developed to predict the temperature rise in RUBD process using response surface methodology (RSM), and the optimum parameters were determined using Genetic Algorithm. Analysis of variance (ANOVA) was carried out at a confidence interval of 95 percent (α = 0.05) to determine the influence of various drilling parameters such as rotational speed, feed rate, drill diameter and abrasive particle size on temperature rise. It was observed that the rotational speed was responsible for the maximum temperature rise (51.8%) followed by drill diameter (18.8%), and abrasive particle size (14.3%); whereas, the feed rate contributed minimal (4%) temperature rise.